How many CCS- and ACS-patients might reach the newly recommended LDL-C-target <55mg/dl in clinical practice if guidelines were applied – an estimate from the DYSIS II study population. (25th November 2020) - Gitt, A.K; Horack, M; Lautsch, D; Zahn, R; Ferrieres, J
Abstract: Background: The 2019 ESC guidelines for the management of dyslipidemia even further lowered the LDL-C-target values for the very high-risk population from <70mg/dl to <55mg/dl. Population based studies already had shown that the previous target was difficult to reach. It is yet unclear how many patients in clinical practice might be treated to the new target. Methods: The Dyslipidemia International Study (DYSIS II) prospectively collected data of patients with chronic coronary syndromes (CCS) and acute coronary syndromes (ACS) (all on statins) in 18 countries in Europe, the Middle East, South- and East Asia to document patient characteristics, medication and a current lipid profile from 2012 to 2014 under real life conditions in physicians' offices and hospitals. We took these real-life lipid profiles and data on the kind/dose of used statins to estimate how treatment escalation such as changing statin treatment to a high dose (atorvastatin ≥40mg / rosuvastatin≥20mg), adding ezetimibe and adding a PCSK9-inhibitor might help to bring LDL-C-levels to the recommended <55mg/dl target. Results: A total of 7, 865 patients were enrolled into DYSIS II, 6, 794 had CCS and 1, 071 ACS. Under the documented statin treatment in DYSIS only 12.7% of patients reached an LDL-C <55mg/dl. Putting all patients on high dose statins in combination with ezetimibe, 64.1% would reach the target. If PCSK9-inhibitors would be used in the remaining patients not at goal a total of 94.0% would match the goal. Conclusion: Our analysis indicates that in real life practice the use available lipid-lowering medications would substantially increase the percentage of CCS- and ACS-patients reaching the newly recommended 2019 ESC guideline LDL-C-target of <55 mg/dl from less than 20% to more than 90% of the population. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): MSD